Cancer of unknown primary is associated with diabetes. Issue 3 (May 2016) - Hemminki, Kari; Försti, Asta; Sundquist, Kristina; Li, Xinjun
Abstract : The incidences of both type 1 diabetes (T1D) and T2D are increasing worldwide. T2D is associated with many cancers. However, no data are available on cancer of unknown primary (CUP), a relatively common, fatal cancer for which tobacco smoking is the only known risk factor. At diagnosis, CUP metastases are found in various organs, which has implications for prognosis. We carried out a nationwide study on the association of CUP with T1D and T2D. 32 600 T1D patients and 178 000 T2D patients were identified from the national healthcare registers and these were linked to the Swedish Cancer Registry. Standardized incidence ratios (SIRs) were calculated for CUP from 1997 through 2010 using anyone without diabetes as a reference. The SIR of CUP in 421 diabetic patients was 1.71, highest for CUP with liver (2.17) and respiratory system (1.95) metastases. The SIR was 2.91 for T1D, but with a small number of patients, 1.38 for T2D with insulin treatment, and 1.78 for the main group of T2D. CUP with liver and respiratory system metastases increased for each diabetic type; however, for T2D, CUP with gastrointestinal and bone metastases also increased. The results provide the first demonstration that CUP is one of the cancers associated with diabetes, with definite evidence on T2D. CUP has a poor prognosis, which may be even worse when diabetes is the underlying comorbidity. A mechanistic question for future work is to determine whether diabetes promotes primaries that escape detection or their metastatic spread.